Improving Interdepartmental Communication in Hospitality Idustry : A Case Study of 4-5 Star Hotel Employees in Phuket - Yulia Lozovitskaya (Prince of Songkla University, 2018)
Thesis (M.B.A., (Hospitality and Tourism Management (International Program)))--Prince of Songkla University, 2017